Hubungan Kecerdasan Adversitas dengan Motivasi Berwirausaha Lulusan Pendidikan Kecakapan Hidup Keterampilan Tata Busana di SKB Kabupaten Lima Puluh Kota - Yela Riyanti; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the low motivation of entrepreneurship that is owned by graduates of life skills education in the field of fashion skills in learning activities in the District of Lima Puluh Kota, seen from 30 graduates who only a few people who are entrepreneurs. Researchers suspect that the cause of the low motivation for entrepreneurship in graduates of Life Skills education is due to the lack of adversity intelligence possessed by graduates. This study aims to describe the relationship between adversity intelligence and entrepreneurial motivation for life skills education graduates in fashion management skills. This research is a quantitative research with a correlational type. The population in this study were 30 people. The sampling technique used was simple random sampling, a sample of 65% as many as 19 people. Data collection techniques using questionnaires and data collection tools using a list of statements (questionnaires). The results of the study showed that the description of adversity intelligence graduates of life skills education in nursing skills was categorized as low.Keywords: Adversity Intelligence, Entrepreneurial Motivation